Evaluation of volatile flavor compounds in bacon made by different pig breeds during storage time. (30th September 2021) - Deng, Siyang; Liu, Yunhe; Huang, Feng; Liu, Jiqian; Han, Dong; Zhang, Chunhui; Blecker, Christophe
Highlights: HS-GC-IMS was first used to identify volatile fingerprints of WP and BP bacons. The type of raw meat play more vital role on flavor of bacon than storage. Volatile compounds detected in WP bacon were much abundant than BP bacon. Abstract: The oxidation and volatile constituents of bacon (which made of white pig (Duroc × Landrace × Yorkshire) and black pig (Beijing Black × Yorkshire)) during refrigerated storage were analyzed by thiobarbituric acid reactive substances (TBARS), total thiol groups, gas chromatography-mass spectrometry (GC–MS) and gas chromatography coupling with ion mobility spectrometry (GC-IMS). The TBARS value of tested samples increased while the total thiol groups decreased during 60 days storage ( P < 0.05). Volatile fingerprint results were obtained by GC–MS and GC-IMS detector, the classes and contents of volatile compounds detected in WP bacon were much abundant than BP bacon. Higher phenols and acids concentrations were observed in WP bacon, while alcohols, ketones, and nitrogen-containing compounds were more determined in BP bacon. Besides, WP bacon was more notably affected by storage rather than BP bacon, and the difference of raw material is the main reason for the flavor in WP and BP bacon comparing with the storage process.